REORIENTASI KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM DALAM MENGHADAPI TANTANGAN GLOBAL - Zulfikar Ali Buto (State Islamic University North Sumatra, 2010)
Abstract: Reorientation of the Competency of the Teachers of Islamic Religious Education and the Global Challenge. In the global era educatorsor teachers of Islamic religious education are requested to develop themselves in such aspects as personal, social and professional competence. In this paper, the author argues that the end result of the lack of these preconditions witness not only in the low standard of education but also in moral degradation of today’s society. On the other hand, he also asserts that by professing such qualification teachers will regain faith from both students and society. This paper then is an attempt to analyze various aspects of competency a religious teacher should consider in facing the ever-increasing challenges in the globalized world.Kata Kunci: kompetensi, guru agama islam, profesional, tantangan global